2012
DOI: 10.1007/s00726-012-1273-3
|View full text |Cite
|
Sign up to set email alerts
|

Taurine deficiency damages retinal neurones: cone photoreceptors and retinal ganglion cells

Abstract: In 1970s, taurine deficiency was reported to induce photoreceptor degeneration in cats and rats. Recently, we found that taurine deficiency contributes to the retinal toxicity of vigabatrin, an antiepileptic drug. However, in this toxicity, retinal ganglion cells were degenerating in parallel to cone photoreceptors. The aim of this study was to re-assess a classic mouse model of taurine deficiency following a treatment with guanidoethane sulfonate (GES), a taurine transporter inhibitor to determine whether ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 53 publications
0
42
0
Order By: Relevance
“…This may also explain why in the nonlight-exposed taurine-depleted animals, we were not able to see rings of cone degeneration even when there is cone loss, because taurine deficiency causes cone loss before rod alteration. 5,9 However, it is still unclear why the cone mosaic is reorganized into rings after photoreceptor loss. It has been suggested that cone rings could be the result of cone migration through processes of Müller cells 81 ; whereas other authors have proposed that it is due to cone death, 68 these studies indicated that rods die in the ''center of the rings'' and photoreceptor (cones and rods) loss expands outward, 27,68 suggesting an interdependence between neighboring photoreceptors.…”
Section: Taurine Depletion Increases Retinal Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…This may also explain why in the nonlight-exposed taurine-depleted animals, we were not able to see rings of cone degeneration even when there is cone loss, because taurine deficiency causes cone loss before rod alteration. 5,9 However, it is still unclear why the cone mosaic is reorganized into rings after photoreceptor loss. It has been suggested that cone rings could be the result of cone migration through processes of Müller cells 81 ; whereas other authors have proposed that it is due to cone death, 68 these studies indicated that rods die in the ''center of the rings'' and photoreceptor (cones and rods) loss expands outward, 27,68 suggesting an interdependence between neighboring photoreceptors.…”
Section: Taurine Depletion Increases Retinal Degenerationmentioning
confidence: 99%
“…The endogenous synthesis of taurine can be insufficient, because in cats 2 and in monkeys 3 nutritional taurine depletion has been shown to cause photoreceptor degeneration. Recently it has been documented that taurine depletion also causes retinal ganglion cell (RGC) loss, [4][5][6] and therefore retinal health is dependent on taurine, at least in some species.…”
mentioning
confidence: 99%
“…Although taurine can be synthesized from endogenous production, the yield is usually inadequate, and thus dietary consumption of taurine is necessary (Kadam and Prabhasankar, 2010). It has been demonstrated that taurine deficiency can lead to renal dysfunction, cardiomyopathy, developmental abnormalities, and severe damage to retinal neurons (Chesney et al, 2010;Gaucher et al, 2012). The influence of taurine on renal physiology includes renal blood flow, glomerular filtration and its rate, osmoregulation, ion reabsorption and secretion, and composition of urine, among others (Chesney et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…18 The parallel degeneration of cone photoreceptors and RGCs was also observed under taurine depletion generated in mice fed with guanidoethane sulfonate (GES), a taurine transporter blocker. 19 The direct effect of taurine on RGCs was then demonstrated using pure RGC cultures and different models of RGC degeneration. 6 Taurine depletion acts synergistically with light to trigger the photoreceptor lesion 9,[20][21][22] and photoreceptor loss appears to be more severe in the dorsal area, as it does for light damage.…”
mentioning
confidence: 99%